Grafting Polymers from Poly(2, 6‐dimethyl‐1, 4‐phenylene oxide) as New Thermoplastics. Issue 11 (24th March 2017) - Zhang, Jiuyang; Wu, Peng
Abstract : In this paper, a kind of thermoplastics based on graft polymers from poly(2, 6‐dimethyl‐1, 4‐phenylene oxide) (PPO) is designed. PPO‐graft polymers show unique properties in various aspects, such as rheological and mechanical behaviors. The graft density shows impact on the relaxation properties of the thermoplastics. This work provides the possibility to use lots of semiflexible engineering polymers as backbones to construct new thermoplastics. Abstract : Graft polymers with poly(2, 6‐dimethyl‐1, 4‐phenylene oxide) (PPO) as backbones are successfully prepared via two convenient steps. The utilization of semiflexible PPO as backbones offers unique properties for the graft polymers. Thermal, rheological, and phase behaviors of these new graft polymers are well controlled via the precise design of architectural parameters. The disordered microphase separation in melt state and the proper composition of side grafts provide the ease of thermal processing for these graft polymers. The graft density shows impact on the relaxation and mechanical properties of the thermoplastics. This work shows the possibility to use lots of semiflexible engineering polymers as backbones to construct new thermoplastics.